Modern methods of reforming delinquent youths - Schild, Clara Dorothy; Hezig, Pauline E. (My University, 1908)
Introduction: One of the most momentous questions to be considered by the thoughtful serious minds of to-day must surely be: how can we best train the rising generation of delinquent children? This question is a vital one because its solution involves not only the welfare and stability of the family, but of the state and nation.
Citation: Schild, Clara Dorothy and Hezig, Pauline E. Modern methods of reforming delinquent youths. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Education; Youth; Children; Graduating theses; Senior theses; Theses